2012
DOI: 10.3389/fnsys.2012.00014
|View full text |Cite
|
Sign up to set email alerts
|

Novel Chalcone-Based Fluorescent Human Histamine H3 Receptor Ligands as Pharmacological Tools

Abstract: Novel fluorescent chalcone-based ligands at human histamine H3 receptors (hH3R) have been designed, synthesized, and characterized. Compounds described are non-imidazole analogs of ciproxifan with a tetralone motif. Tetralones as chemical precursors and related fluorescent chalcones exhibit affinities at hH3R in the same concentration range like the reference antagonist ciproxifan (hH3R pKi value of 7.2). Fluorescence characterization of our novel ligands shows emission maxima about 570 nm for yellow fluoresce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 30 publications
0
27
0
Order By: Relevance
“…77 Stark et al reported a series of chalcone analogues ( 4 ) that could be used to image human histamine H3 receptors (hH3R) in stably transfected HEK-293 cells. 78 Fluorescent chalcones have also been applied to image stem cells. 54,79 For example, Lee et al designed a novel library of 160 fluorescent chalcone amide compounds.…”
Section: Fluorescent Properties Of Chalconesmentioning
confidence: 99%
“…77 Stark et al reported a series of chalcone analogues ( 4 ) that could be used to image human histamine H3 receptors (hH3R) in stably transfected HEK-293 cells. 78 Fluorescent chalcones have also been applied to image stem cells. 54,79 For example, Lee et al designed a novel library of 160 fluorescent chalcone amide compounds.…”
Section: Fluorescent Properties Of Chalconesmentioning
confidence: 99%
“…In another report of an H 3 R fluorescent ligand, but with a goal of making red‐shifted probes, Tomasch et al ., (2012c) have tethered selective H 3 R antagonists, again based on a piperidine moiety, to substituted chalcones. A series of pharmacophore–fluorophore combinations containing different linker positions and lengths were synthesized, and all exhibited nanomolar affinity for the human H 3 R and selectivity over the H 1 R (one log unit) and H 4 R (two log units).…”
Section: Fluorescent Ligands For Gpcrsmentioning
confidence: 99%
“…Synthesis of the fluorophore moiety was completed by reaction with boron trifluoroetherate as the final reaction in a stepwise synthesis, rather than the more common convergent approach of coupling a pre‐activated (and often commercially available as the NHS ester) fluorophore to a complementary pharmacophore/linker. Conjugate 19 , named Bodilisant by the authors, displayed a low nanomolar affinity for the human H 3 R that was 10 times more potent that the previous generation ( 16 – 18 ) of conjugates (Tomasch et al ., 2012c). Again, H 3 R subtype selectivity was maintained.…”
Section: Fluorescent Ligands For Gpcrsmentioning
confidence: 99%
“…There are many efforts to design fluorescent GPCR ligands on the strength of their prominence as the largest and most versatile group of cell surface receptors, therefore responsible for various pharmacological functions. 8,9 Recent research in our working group resulted in chalconebased fluorescent hH 3 R ligands able to label hH 3 R in cells and human tissue 10 based on earlier results (Mirisant-405, Mirisant-470, and Benz-Mirisant-405).…”
mentioning
confidence: 99%
“…There are many efforts to design fluorescent GPCR ligands on the strength of their prominence as the largest and most versatile group of cell surface receptors, therefore responsible for various pharmacological functions. 8,9 Recent research in our working group resulted in chalconebased fluorescent hH 3 R ligands able to label hH 3 R in cells and human tissue 10 based on earlier results (Mirisant-405, Mirisant-470, and Benz-Mirisant-405).11−13 Because these early ligands were not usable under all conditions, we wanted to design fluorescent hH 3 R ligands with more properties in common in one molecule, that is, higher hH 3 R affinity, versatile fluorescent wavelength, optimized fluorescence intensity, and thus a better signal-to-noise ratio. The decision has been made for 4,4-difluoro-4-bora-3a,4a-diaza-s-indacene (BODIPY) dye as a fluorophore due to its high extinction coefficient, its sharp fluorescence emission peaks with high quantum yield, 14 its insensitivity to pH and solvent polarity, and its greater chemical and photochemical stability.…”
mentioning
confidence: 99%